2017
DOI: 10.1073/pnas.1714895114
|View full text |Cite
|
Sign up to set email alerts
|

Development of functional ectopic compound eyes in scarabaeid beetles by knockdown of orthodenticle

Abstract: Complex traits like limbs, brains, or eyes form through coordinated integration of diverse cell fates across developmental space and time, yet understanding how complexity and integration emerge from uniform, undifferentiated precursor tissues remains limited. Here, we use ectopic eye formation as a paradigm to investigate the emergence and integration of novel complex structures following massive ontogenetic perturbation. We show that down-regulation via RNAi of a single head patterning gene-orthodenticle-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
(37 reference statements)
0
9
0
1
Order By: Relevance
“…More anecdotal, the recent discovery of a python with a third functioning eye on its forehead could also be related to the macroevolution process (https://www.livescience.com/65382-three-eyedsnake.html). Similar ectopic induction of functional eyes has been genetically induced in scarab beetles [60]. The rapid emergence and integration of novel complex organs such as a eye or an extra finger provide remarkable examples of the ability of developmental systems to channel massive perturbations toward orderly and functional outcomes, highlighting the extraordinary plasticity of genome and the buffering capacity of developmental systems.…”
Section: Chromoanagenesis and Saltational Evolutionmentioning
confidence: 78%
“…More anecdotal, the recent discovery of a python with a third functioning eye on its forehead could also be related to the macroevolution process (https://www.livescience.com/65382-three-eyedsnake.html). Similar ectopic induction of functional eyes has been genetically induced in scarab beetles [60]. The rapid emergence and integration of novel complex organs such as a eye or an extra finger provide remarkable examples of the ability of developmental systems to channel massive perturbations toward orderly and functional outcomes, highlighting the extraordinary plasticity of genome and the buffering capacity of developmental systems.…”
Section: Chromoanagenesis and Saltational Evolutionmentioning
confidence: 78%
“…In a follow-up study, Zattara et al were able to show that one of the patterning genes critical for establishing said boundary during embryogenesis-otdhas been repurposed during late larval development to pattern the medial dorsal head. otd RNAi phenotypes reported by Zattara et al included a reduction or loss of posterior head horns, the expression of ectopic horns in more anterior locations, and-curiously-the induction of ectopic medial compound eyes [11,37]. Collectively, the results of these two studies motivated the suspicion that the positioning and integration of horns within the posterior head may be enabled by the repurposing of genes and developmental processes already involved in patterning the corresponding regions during earlier developmental stages, and in addition may to some degree involve network components ancestrally associated with the induction and positioning of eyes including ocelli.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work by Zattara et al . [ 25 ] found that RNAi-mediated otd attenuation in Onthophagus beetles resulted in the development of CEs on the dorsal head. These authors acknowledge that most beetle families have lost ocelli and speculate that otd attenuation might have triggered the atavistic ocellar program expressed as CE [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, medial head identity would be regulated by wg through two mechanisms: establishing an otdþ/ey2 domain where ocelli develop, and by preventing dpp expression and/or signalling (figure 2g; see [10,24]). Recent work by Zattara et al [25] found that RNAi-mediated otd attenuation in Onthophagus beetles resulted in the development of CEs on the dorsal head. These authors acknowledge that most beetle families have lost ocelli and speculate that otd attenuation might have triggered the atavistic ocellar program expressed as CE [25].…”
Section: Discussionmentioning
confidence: 99%